9.3k views
5 votes
if h(x)=5+c and k(h)=1/x, which expression is equivalent to (k•h)(x) a. (5+x)/x b.1/(5+x) c. 5+(1/x) d. 5+(5+x)

User Vmrvictor
by
5.3k points

2 Answers

7 votes

Answer:

A. (5 + x) / x

Explanation:

h(x) = 5 + x

k(h) = 1 / x

express the above to (k*h)(x)

(k*h)(x) = (1 / x) * (5 + x)

= 1/x (5+x)

= 1 * (5 + x)

x

= 1 (5 + x) = 5 + x

= 5 + x

x

User Sdrevk
by
5.2k points
4 votes

Answer:

A

Explanation:

We are given the two functions:


\displaystyle h(x)=5+x \text{ and } k(x) = (1)/(x)

And we want to find:


(k\cdot h)(x)

Recall that this is equivalent to:


\displaystye (k\cdot h)(x) = k(x) \cdot h(x)

Substitute and simplify:


\displaystyle \begin{aligned} (k\cdot h)(x) & = \left((1)/(x)\right)(5+x) \\ \\ & = (5+x)/(x) \end{aligned}

In conclusion, our answer is A.

User Baseem Najjar
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.